Beispiel Nr: 06
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 7 x +1\frac{1}{2} y =1\\ 2 x -5 y = 22 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 7 x +1\frac{1}{2} y =1\\ II \qquad 2 x -5 y = 22 \\ \text{I nach y auflösen}\\ 7 x +1\frac{1}{2} y =1 \\ 7 x +1\frac{1}{2} y =1 \qquad /-7 x\\ 1\frac{1}{2} y =1 -7 x \qquad /:1\frac{1}{2} \\ y =\frac{2}{3} -4\frac{2}{3} x \\ \text{II nach y auflösen}\\ 2 x -5 y =22 \\ 2 x -5 y =22 \qquad /-2 x\\ -5 y =22 -2 x \qquad /:\left(-5\right) \\ y =-4\frac{2}{5} +\frac{2}{5} x \\ \text{I = II}\\ \frac{2}{3} -4\frac{2}{3} x =-4\frac{2}{5} +\frac{2}{5} x \qquad /+4\frac{2}{3} x /+4\frac{2}{5} \\ \frac{2}{3}+4\frac{2}{5} =\frac{2}{5} x +4\frac{2}{3} x \\ 5\frac{1}{15} =5\frac{1}{15} x \qquad /:5\frac{1}{15} \\ x=1 \\ \text{x in I}\\ y =\frac{2}{3} -4\frac{2}{3} \cdot 1 \\ y=-4 \\ L=\{1/-4\} \end{array} & \begin{array}{l} I \qquad 7 x +1\frac{1}{2} y =1\\ II \qquad 2 x -5 y = 22 \\ \text{I nach x auflösen}\\ 7 x +1\frac{1}{2} y =1 \\ 7 x +1\frac{1}{2} y =1 \qquad /-1\frac{1}{2} y\\ 7 x =1 -1\frac{1}{2} y \qquad /:7 \\ x =\frac{1}{7} -\frac{3}{14} y \\ \text{II nach x auflösen}\\ 2 x -5 y =22 \\ 2 x -5 y =22 \qquad /+5 y\\ 2 x =22 +5 y \qquad /:2 \\ x =11 +2\frac{1}{2} y \\ \text{I = II}\\ \frac{1}{7} -\frac{3}{14} y =11 +2\frac{1}{2} y \qquad /+\frac{3}{14} y /-11 \\ \frac{1}{7}-11 =2\frac{1}{2} y +\frac{3}{14} y \\ -10\frac{6}{7} =2\frac{5}{7} y \qquad /:2\frac{5}{7} \\ y=-4 \\ \text{y in I}\\ x =\frac{1}{7} -\frac{3}{14} \cdot -4 \\ x=1 \\ L=\{1/-4\} \end{array} \end{array} $